STUDY OF FITNESS FOR SERVICE AND REMAINING STRENGTH ANALYZE FOR CRACKLIKE FLAW AND DISTORTION SHELL AT PIPELINE BASED ON API RP 579 - FIKRIE AHMAD FIRMANSYAH (NIM : 13104037); Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja ,
During it’s safe operated, then the fitness for service is not conducted, just need routine ordinary maintenance. Otherwise, when after exceed inspection period, and it’s founded the crack defect (cracklike flaw) or geometric defect (distortion shell), then it’s need fitness for service assessment which aim to determine the remaining strength, this one is related with RBI process for pull to failure and damage by degradation of defect.The fitness for service assessment is a set of quantitative used in RBI process to determine the integrity and remaining life of degraded static component. In this final project, we analyze the integrity and remaining strength at the pipeline based on API recommended practice 579 section 8 & 9,fitness for service assessment is performed to make sure that process plant equipment, such as Piping, pipeline, tanks, and pressure vessel, will operate safely and reliably for some desired future period and to make run or repair decisions. In the case study, the assessment of the component need the evaluating after level 1 & in API RP 579, until level 3, there is analyze stress with the finite element., each component will be reduced the pressure that approximate 10 % until that near has safety factor is 1. If the Safety factor not until 1 so the evaluating mus t be to repaired, retired,or replacement, then after the case study is conclude, that all component, which experienced failure, mainly in bulge for ratio of stress until below 1, for dent has safety factor below 1, and crack not save for level2.